Higher platelet activity is present in patients with restenosis after percutaneous coronary intervention compared with patients with an occlusion of coronary artery bypass graft - Osmančík, Pavel; Bednář, František; Pávková, Leona; Toušek, Petr; Štros, Petr; Jirásek, Karel (Blood coagulation & fibrinolysis, 2008)
The aim of the study was to compare platelet activity between patients with an occlusion of bypass graft after coronary artery bypass graft surgery and restenosis after percutaneous coronary intervention (PCI); that is, between patients with reappearance of ischemia after two different kinds of coronary revascularization. Thirty patients were studied in a cross-sectional designed study. Fifteen of them were patients with the worst bypass graft patency from Prague-4 study (control protocol-driven coronary angiography performed at 1 year after surgery; originally 47 bypass grafts implanted, 94% of venous grafts occluded). The remaining 15 were patients with restenosis 3-12 months after PCI. Blood samples were drawn at least 12 weeks after coronary angiography. Platelet activity was determined by membrane expression of P-selectin (CD62P, % of positive cells) by flow cytometry, aggregability by ADP aggregometry. Data are expressed as mean +/- SEM. Both groups were similar with respect to age, BMI and presence of diabetes mellitus. No patient suffered from acute coronary syndrome. P-selectin expression was significantly higher in the patients with restenosis compared with patients with bypass graft occlusion (1.96 +/- 0.07 vs. 0.77 +/- 0.03, P < 0.001, Wilcoxon test). ADP aggregometry was not different between groups (55.5 +/- 1.1 vs. 56.1 +/- 0.8, P = NS). Higher platelet activity is present in the patients with restenosis after PCI compared with the patients with the occlusion of bypass graft. Platelet activity play more important role in the development of restenosis after PCI compared with the occlusion of bypass graft after coronary artery bypass graft surgery, at least in the period up to 1 year after revascularization.
Keywords: aktivace trombocytů; financování organizované; Platelet Activation; revaskularizace myokardu; Female; Myocardial Ischemia; balónková koronární angioplastika; ženské pohlaví; průřezové studie; koronární restenóza; Myocardial Revascularization; lidé; Coronary Restenosis; ischemická choroba srdeční; Graft Occlusion, Vascular; Middle Aged; Financing, Organized; Cross-Sectional Studies; Male; Aged; Angioplasty, Balloon, Coronary; okluze cévního štěpu; koronární bypass; lidé středního věku; senioři; mužské pohlaví; Coronary Artery Bypass; Humans